Engineered/designer biochar for the removal of phosphate in water and wastewater - Vikrant, Kumar; Kim, Ki-Hyun; Ok, Yong Sik; Tsang, Daniel C.W.; Tsang, Yiu Fai; Giri, Balendu Shekhar; Singh, Ram Sharan (The Science of the total environment, 2018)
•The control of excess aqueous phosphate is a crucial task in environmental management.•Elevated levels of phosphate in water systems can increase the costs of water treatment.•The easy fabrication and structural flexibility of biochars ensure the efficient removal of P.•We propose various options to apply biochars in the area of phosphate sorption and separation. [Display omitted] During the past decade, biochar has attracted immense scientific interest for agricultural and environmental applications. A broad range of biochars with advantageous properties (e.g., high surface area, flexible architecture, and high porosity) has been developed for pollution abatement. Nevertheless, biochar suffers from certain drawbacks (e.g., limited sorption capacity for anions and poor mechanical properties) that limit their practical applicability. This review focuses on recent advancements in biochar technology, especially with respect to its technical aspects, the variables associated with removing phosphates from water, and the challenges for such abatement. The attention paid to the specific remediation of phosphate from water using biochar is limited (n=1114 – Scopus) compared to the application of biochar to other common water pollutants (n=3998 – Scopus). The subject warrants immediate rigorous research because of the undesirable effects of excess phosphate in water bodies. This review will thus facilitate the construction of a roadmap for further developments and the expansion of this challenging area of research.